Investigation of the Axial Force Compensation and Deformation Control Effect of Servo Steel Struts in a Deep Foundation Pit Excavation in Soft Clay - Honggui Di; Huiji Guo; Shunhua Zhou; Jinming Chen; Lu Wen (Advances in Civil Engineering)
This study presents a comparative analysis of the deformation control effect of the hydraulic servo steel struts and ordinary steel struts of a foundation pit based on the measured axial force of the steel struts, lateral wall deflection, and ground surface settlement due to pit excavation. The results indicate that ordinary steel struts installed via axial preloading exhibit a disadvantageous axial force loss with a maximum value equal to 86.7% of the axial preloading force. When compared with ordinary steel struts, the hydraulic servo steel strut exhibits a superior supporting effect. The hydraulic servo steel strut adjusts the axial force in real time based on the deformation of the retaining structure and the axial force of the struts. Thus, the ratio of maximum lateral deflection to the excavation depth of a deep foundation pit in soft soil is less than 0.3%. Concrete struts undergo unsupported exposure during the excavation process, leading to sharply increasing deformation of the retaining structure. Therefore, regarding a foundation pit with strict requirements for deformation control, the use of hydraulic servo steel struts rather than concrete struts is recommended.